An observation-based method to quantify the human influence on hydrological drought: upstream–downstream comparison. Issue 3 (17th February 2019) - Rangecroft, Sally; Van Loon, Anne F.; Maureira, Héctor; Verbist, Koen; Hannah, David M.
ABSTRACT: In this present era of the Anthropocene, human activities affect hydrology and droughts. Quantifying this human influence improves our understanding and builds fundamental knowledge for water resource management. Analysis of observation data is useful in progressing this knowledge as these human activities and feedbacks are intrinsically included. Therefore, here we present an observation-based approach, the upstream–downstream comparison, to quantify changes in hydrological drought downstream of a human activity. We demonstrate this approach in a basin in northern Chile, where a reservoir was introduced. A sensitivity analysis is performed to assess how different choices of drought analysis threshold can affect the results and interpretation. We find that many commonly used choices do not exclude human activities from the threshold and therefore could be underestimating the change detected due to the human influence. The upstream–downstream comparison avoids this through the application of the upstream station threshold rather than the human-influenced downstream station.